2010
DOI: 10.1089/sur.2009.072
|View full text |Cite
|
Sign up to set email alerts
|

A Wound Protector Shields Incision Sites from Bacterial Invasion

Abstract: These results suggest that the WP protects an incision site from bacterial invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 8 publications
(8 reference statements)
2
32
0
Order By: Relevance
“…It also supports the statement that various measures for the control of the superficial SSI can be highly effect ive. 32 Like other authors, 33 we observed seasonal variations in the frequency of fungi, with lower levels in autumn and winter; however, the most common fungus in our study was Penicillum rather than the previously reported Aspergillus. With regard to the number of CFU found in our study, these were quite low compared with the levels published elsewhere 34 in studies that observed the lowest levels of CFU in operating rooms with 12 ± 14 CFU/m 3 .…”
Section: Environmental Biosafety Factorssupporting
confidence: 76%
“…It also supports the statement that various measures for the control of the superficial SSI can be highly effect ive. 32 Like other authors, 33 we observed seasonal variations in the frequency of fungi, with lower levels in autumn and winter; however, the most common fungus in our study was Penicillum rather than the previously reported Aspergillus. With regard to the number of CFU found in our study, these were quite low compared with the levels published elsewhere 34 in studies that observed the lowest levels of CFU in operating rooms with 12 ± 14 CFU/m 3 .…”
Section: Environmental Biosafety Factorssupporting
confidence: 76%
“…The use of the Alexis wound protector has been reported to protect surgical wounds from contamination by bacteria and, consequently, to prevent infection during gastrointestinal surgery. 9 Horiuchi et al 10 reported that the use of the Alexis retractor at incision sites during gastric and colorectal surgery significantly reduced the incidence of wound infections (superficial infections at the sites of surgical incisions) in a randomized controlled study. The same wound protector also significantly reduced the risk of wound complications in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for SSI limited to laparoscopic colon resection have been reported to include increased BMI and a history of DM (11)(12)(13). Wound retractors can prevent infection after laparoscopic colorectal procedures, indicating that the methods and instruments used are important (14,15). In our department, the incidence of ANTICANCER RESEARCH 38: 513-517 (2018) 514 transumbilical wound SSI in LAC was 4.3% (15/348).…”
Section: Discussionmentioning
confidence: 83%